1999
DOI: 10.1093/rheumatology/38.7.602
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid in the treatment of osteoarthritis of the knee

Abstract: The study demonstrated that five weekly intra-articular injections of sodium hyaluronate (Hyalgan) were superior to placebo and well tolerated in patients with osteoarthritis of the knee with a symptomatic benefit which persisted for 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(135 citation statements)
references
References 0 publications
7
123
0
5
Order By: Relevance
“…It is a linear natural polysaccharide composed of the repeating disaccharide b-1-4-D-glucuronic acid and b-1-3-N-acetyl-D-glucosamine units. Since HA is a primary ECM component, it has been investigated as scaffolding material for soft tissue engineering applications [1][2][3][4]. HA is biocompatible and a key component in bone and cartilage tissue engineering applications, and thus, a wide range of additional biomedical applications have also been explored [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is a linear natural polysaccharide composed of the repeating disaccharide b-1-4-D-glucuronic acid and b-1-3-N-acetyl-D-glucosamine units. Since HA is a primary ECM component, it has been investigated as scaffolding material for soft tissue engineering applications [1][2][3][4]. HA is biocompatible and a key component in bone and cartilage tissue engineering applications, and thus, a wide range of additional biomedical applications have also been explored [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The 14 studies left were reviewed in chronological order (Fig 1). 4,12,[17][18][19][20][21][22][23][24][25][26][27][28] study 1…”
Section: Resultsmentioning
confidence: 99%
“…24,26,27 Finally, two studies showed a modest effect in favour of HA over placebo for pain that was noticeable at six months but not for function. 23,28 Of the two studies that compared HA with steroid injections, one showed no statistically significant difference between the two groups. 12 The other suggested that HA was better at six months than steroid injections but this study had a very high drop out rate at six months, 19 making the results questionable.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations